Current account dynamics and the housing cycle in Spain - Maas, Daniel Peter; Mayer, Eric; Rüth, Sebastian (Journal of international money and finance, 2018)
We investigate the negative correlation between housing markets and the current account in a monetary union, using the Spanish economy as an illustrative example. By employing robust sign restrictions, which we derive from a DSGE model for a currency union, we analyze the effects of Spanish pull and Eurozone push factors in a mixed-frequency VAR framework. Savings glut, risk premium, and housing bubble shocks are capable of generating the negative co-movement of housing markets and the current account in the data. In contrast—and counterfactual to the housing boom—financial easing shocks in Spain predict a decline in both residential investment and house prices.
Gesehen am 01.03.2021